المفارقة الزمنية في رواية "عندما تشيخ الذئاب" لجمال الناجي - وفاء منصوري (My University, 2025)
The thesis entitled “Temporal Anachrony in Narrative Fiction: A Structural and Functional Analysis” presents an in-depth study of how time operates within narrative texts—not merely as a backdrop for events, but as an active structural element that contributes to meaning-making and guides reader reception. The research is grounded in a central question: How is time restructured in modern narrative discourse? And what semantic and aesthetic functions does temporal anachrony fulfill within the architecture of the text? The study draws on the theoretical framework established by Gérard Genette, particularly in his work Narrative Discourse, where he distinguishes between story time (the actual chronological sequence of events) and narrative time (the order in which the narrator chooses to present those events). From this discrepancy arises what is known as “temporal anachrony,” which primarily manifests through the techniques of analepsis (flashback) and prolepsis (foreshadowing), with nuanced subcategories (external/internal, complete/partial, etc.). The thesis highlights how temporal anachrony functions as a rhetorical and narrative device that enriches the text, builds suspense, deepens the psychological structure of characters, and disrupts traditional linear temporality. It also demonstrates how this technique reshapes the relationship between reader and text, opening the door to multiple interpretations—especially in novels that explore themes of identity, memory, and alienation. On the applied level, the thesis analyzes examples from contemporary Arabic novels, such as The Beaver by Mohammed Hassan Alwan, where analepsis is used to deconstruct the protagonist’s psychological time, and Sintra by Hassan Aourid, which employs temporal shifts to express fragmented identity. The study also suggests that temporal anachrony may transcend its narrative function to touch on philosophical dimensions, where time itself becomes an object of contemplation and doubt. Ultimately, the thesis concludes that temporal anachrony is not merely a stylistic device, but a meaning-bearing structure that reshapes the narrative from within. It reflects a contemporary narrative vision that dismantles traditional chronology in favor of a layered temporal construction—one that mirrors the complexity of human experience and the interweaving of temporalities within individual and collective consciousness. Thus, the thesis affirms that temporal anachrony is not only a creative narrative technique, but also a philosophical lens through which the novel can express memory, forgetting, and existential anxiety with depth and beauty. It invites a rethinking of time—not as a linear stream, but as an intricate fabric that weaves the fate of characters and reflects the fragmentation of the modern self. ---------------------- تتناول مذكرة بعنوان "المفارقة الزمنية في السرد الروائي: تحليل بنيوي ووظيفي" دراسة معمّقة لكيفية اشتغال الزمن داخل النصوص السردية، ليس بوصفه مجرد خلفية للأحداث، بل كعنصر بنائي فاعل يُسهم في تشكيل المعنى وتوجيه التلقي. تنطلق المذكرة من إشكالية مركزية مفادها: كيف يُعاد ترتيب الزمن في الخطاب الروائي الحديث؟ وما الوظائف الدلالية والجمالية التي تحققها المفارقة الزمنية في بنية النص؟ تعتمد الدراسة على الإطار النظري الذي وضعه جيرار جينيت، خاصة في كتابه "خطاب الحكاية"، حيث يُفرّق بين زمن القصة (الترتيب الفعلي للأحداث) وزمن الخطاب (الترتيب الذي يختاره السارد لرواية الأحداث). ومن هذا التفاوت ينشأ ما يُعرف بـ"المفارقة الزمنية"، التي تتجلى أساسًا في تقنيتي الاسترجاع (العودة إلى الماضي) والاستباق (الإشارة إلى المستقبل)، مع تصنيفات فرعية دقيقة (خارجي/داخلي، تام/جزئي، إلخ). تُبرز المذكرة كيف أن المفارقة الزمنية تُستخدم كأداة بلاغية وسردية تُثري النص، وتُسهم في بناء التوتر، وتعميق البنية النفسية للشخصيات، وكسر خطية الزمن التقليدي. كما تُظهر كيف أن هذه التقنية تُعيد تشكيل العلاقة بين القارئ والنص، وتفتح المجال لتعدد التأويلات، خاصة في الروايات التي تتناول قضايا الهوية، الذاكرة، والاغتراب. في الجانب التطبيقي، تُحلل المذكرة نماذج من الرواية العربية الحديثة، مثل القندس لمحمد حسن علوان، حيث يُوظف الاسترجاع لتفكيك الزمن النفسي للشخصية، وسينترا لحسن أوريد، التي تُبرز التقديم والتأخير كأدوات تعبير عن اضطراب الهوية. كما تُشير إلى أن المفارقة الزمنية قد تتجاوز البُعد الزمني لتُلامس البُعد الفلسفي، إذ يُصبح الزمن ذاته موضوعًا للتأمل والشك. وتخلص الدراسة إلى أن المفارقة الزمنية ليست مجرد تقنية شكلية، بل هي بنية دلالية تُعيد تشكيل النص من الداخل، وتُعبّر عن رؤية سردية معاصرة تُقوّض التسلسل الزمني التقليدي لصالح بناء زمني متعدد ---------------------- Le mémoire intitulé « L’anachronie dans le récit romanesque : analyse structurelle et fonctionnelle » propose une étude approfondie du fonctionnement du temps dans les textes narratifs, non pas comme simple toile de fond des événements, mais comme un élément structurel actif contribuant à la construction du sens et à l’orientation de la réception. Le mémoire part d’une problématique centrale : comment le temps est-il réorganisé dans le discours romanesque moderne ? Et quelles sont les fonctions sémantiques et esthétiques que l’anachronie accomplit dans la structure du texte ? L’étude s’appuie sur le cadre théorique élaboré par Gérard Genette, notamment dans son ouvrage Discours du récit, où il distingue le temps de l’histoire (l’ordre réel des événements) du temps du discours (l’ordre choisi par le narrateur pour raconter ces événements). C’est de cet écart que naît ce qu’on appelle « anachronie », qui se manifeste principalement à travers deux techniques : l’analepse (retour en arrière) et la prolepse (anticipation), avec des sous-catégories précises (externe/interne, totale/partielle, etc.). Le mémoire met en lumière comment l’anachronie est utilisée comme un outil rhétorique et narratif qui enrichit le texte, construit la tension, approfondit la structure psychologique des personnages et rompt avec la linéarité temporelle traditionnelle. Il montre également comment cette technique reconfigure la relation entre le lecteur et le texte, ouvrant la voie à une pluralité d’interprétations, notamment dans les romans abordant les thèmes de l’identité, de la mémoire et de l’aliénation. Sur le plan pratique, le mémoire analyse des exemples issus du roman arabe contemporain, tels que Le Castor de Mohammed Hassan Alwan, où l’analepse est utilisée pour déconstruire le temps psychologique du personnage, et Sintra de Hassan Aourid, qui met en avant l’usage de l’anticipation et du retour en arrière comme moyens d’exprimer une identité troublée. L’étude souligne également que l’anachronie peut dépasser la simple dimension temporelle pour toucher à une dimension philosophique, où le temps devient lui-même objet de réflexion et de doute. En conclusion, le mémoire affirme que l’anachronie n’est pas une simple technique formelle, mais une structure porteuse de sens qui reconfigure le texte de l’intérieur, exprimant une vision narrative contemporaine qui déconstruit la chronologie traditionnelle au profit d’une construction temporelle stratifiée, reflétant la complexité de l’expérience humaine et l’entrelacement des temporalités dans la conscience individuelle et collective.
Keywords: : l’anachronie – le roman quand les loups vieillissent; المفارقة الزمنية – رواية عندما تشيخ الذئاب